Penerapan Konseling Kelompok Dengan Teknik Behavioral Rehearsal Untuk Membentuk Kemandirian Remaja Di Panti Asuhan Bunda - Nindi Zila Mareti; Suryati Suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Application of Group Counseling Using Behavioral Rehearsal Techniques to Form Adolescent Independence in the Bunda Orphanage". The purpose of this study was to find out the description of adolescent learning independence, as well as to determine group counseling strategies with behavioral rehearsal techniques in forming adolescent learning independence at the Bunda Orphanage. This type of research is descriptive research with a qualitative approach, data collection tools interview, observation, and documentation. The subjects in this study were five teenagers and one chairman of the board. The data analysis techniques used were: data reduction, data presentation, and conclusions or verification. The results of this study indicate that independent learning in adolescents can be seen from being responsible, creative, progressive, self-control, and self-confidence. Group counseling strategies with behavioral rehearsal techniques to form adolescent learning independence are the initial stage, the transitional stage, the activity stage, and the final stage, and the stages in the behavioral rehearsal technique are practicing exemplary behavior, building client motivation, giving clients feedback, speaking as a person. first, agreeing to the counselor's praise, and trying new things that can shape learning independence.